Pembuatan Sabun Cuci Piring dari Minyak Jelantah untuk Mengurangi Limbah Rumah Tangnga di Desa Padang Luas Kampar - Syamsu Kamarullah; Daniel Firmansyah; Fahmi Satrio Wicaksono; Naufal Rasyid; Hana Shepia; Melinda Sari; Nadira Rizal Putri; Nurhafifah Nasri; wiji Paluvi Lasari; Trisna Marliana Sari; Guslinda Guslinda (LP2M Universitas Muhammadiyah Enrekang, 2022)
Soap is a compound of sodium or potassium with fatty acids from vegetable oils or animal fats in solid, soft or liquid form, and foams. This soap is made from waste cooking oil. This service activity aims to provide information and direct education about the use of used cooking oil waste into dish soap. In addition, it also carries out sustainable environmental protection, which is generally applied to environmentally friendly chemicals. The method used in the training in making dish soap is through a demonstration method or direct practice. The result of this service is the introduction and use of dish soap in the local community.